109k views
9 votes
(-3x2 + 6x - 12) + (5x + 9) is equivalent to expression __

User Lokinou
by
6.1k points

2 Answers

5 votes

Answer:

see below

Explanation:

Here are the simplified results of each polynomial combination.

(5x2 + 2x + 1) + (6x2 − 3x + 9)

= 5x2 + 2x + 1 + 6x2 − 3x + 9

= 5x2 + 6x2 + 2x − 3x + 1 + 9

= 11x2 − x + 10 (B)

(-3x2 + 6x − 12) + (5x + 9)

= -3x2 + 6x − 12 + 5x + 9

= -3x2 + 6x + 5x − 12 + 9

= -3x2 + 11x − 3 (A)

(8x + 16) − (3x2 − 3x − 15)

= 8x + 16 − 3x2 + 3x + 15

= -3x2 + 8x + 3x + 16 + 15

= -3x2 + 11x + 31 (D)

(5x2 + 23x − 7) − (x2 − 4x + 21)

= 5x2 + 23x − 7 − x2 + 4x − 21

= 5x2 − x2 + 23x + 4x − 7 − 21

= 4x2 + 27x − 28 (C)

User Herta
by
5.3k points
7 votes

Answer:


-3x^(2)+11x-3

Explanation:


(-3x^(2)+6x-12)+(5x+9) = -3x^(2) + 6x - 12 + 5x + 9 = -3x^(2) + 11x - 3

User Synic
by
5.5k points